2002
DOI: 10.1159/000064430
|View full text |Cite
|
Sign up to set email alerts
|

The Amygdala Regulates the Pituitary-Adrenocortical Response and Release of Hypothalamic Serotonin following Electrical Stimulation of the Dorsal Raphe Nucleus in the Rat

Abstract: The amygdala is known to modulate the function of the hypothalamo-pituitary-adrenocortical (HPA) axis, but the mechanism of this effect is still not clear. In the present study we examined the specific role of the serotonin (5-HT) system in mediating the effect of the amygdala on the activity of the HPA axis. Bilateral lesions of the amygdala in rats reduced the adrenocorticotropin (ACTH) and corticosterone responses to electrical stimulation of the dorsal raphe nucleus, where the cell bodies of serotonergic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 29 publications
0
29
0
5
Order By: Relevance
“…We have previously demonstrated that the activation of central AMG has a facilitatory efect on the function of the dorsal raphe nucleus 5-HT neurons, which project to the PVN, suggesting a mechanism by which this structure may modulate the HPA axis responses [31]. In particular, we examined the role of the central AMG in modulating the HPA axis responses to speciic hypothalamic noradrenergic and glutamate stimulation.…”
Section: Direct Adrenergic and Glutamate Stimulation Of The Hypothalamusmentioning
confidence: 97%
See 2 more Smart Citations
“…We have previously demonstrated that the activation of central AMG has a facilitatory efect on the function of the dorsal raphe nucleus 5-HT neurons, which project to the PVN, suggesting a mechanism by which this structure may modulate the HPA axis responses [31]. In particular, we examined the role of the central AMG in modulating the HPA axis responses to speciic hypothalamic noradrenergic and glutamate stimulation.…”
Section: Direct Adrenergic and Glutamate Stimulation Of The Hypothalamusmentioning
confidence: 97%
“…It has been demonstrated that these projections include neurons containing CRH that in this case function as a neurotransmiter in the AMG. These neurons activate, noradrenergic and serotonergic output from brainstem nuclei [26,28,30,31]. These nuclei play an essential role in the activation of the HPA axis upon exposure to stressful stimuli, including immune challenges [32].…”
Section: Viral Infection Of the Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that the activity of the amygdala is associated with the HPA axis through serotonergic projections to the hypothalamus (Weidenfeld et al 2002), influencing the stress response (Herman et al 2005). It has also been suggested that the central amygdaloid nucleus takes part in overproduction of CRF in melancholic patients with hypercortisolaemia (Reul & Holsboer, 2002).…”
Section: Mineralocorticoid Receptormentioning
confidence: 99%
“…During the early postnatal period, 5-HT plays a pivotal role in the development of the CNS (Buznikov et al, 2001), and 5-HT neurotransmission is involved in both activation and feedback control of the neuroendocrine stress axis (Weidenfeld et al, 2002). In turn, stress hormones are also involved in regulating the expression of certain serotonin system genes, including that for the serotonin transporter (SERT) (Tafet et al, 2001).…”
Section: Introductionmentioning
confidence: 99%